From Ganglion Cell to Photoreceptor Layer: Timeline of Deterioration in a Rat Ischemia/Reperfusion Model - Palmhof, Marina; Frank, Viktoria; Rappard, Pascal; Kortenhorn, Emely; Demuth, Julia; Biert, Nora; Stute, Gesa; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Cellular Neuroscience, 2019)
Neuronal damage and impaired vision in different retinal disorders are induced, among other factors, by ischemia/reperfusion (I/R). Since the mechanisms and the progression of ischemic injury are still not completely clarified, a timeline of this retinal degeneration is needed. In this study, we investigated protein and mRNA alterations at 2, 6, 12, and 24 h as well as 3 and 7 days after ischemia to determine the course of an ischemic insult through the whole retina. Moreover, functional analyses were performed at later stages. We detected a significant functional loss of cells in the inner nuclear layer and photoreceptors at 3 and 7 days. Additionally, the thickness of the whole retina was decreased at these points in time, indicating a severe degradation of all retinal layers. Immunohistological and qRT-PCR analyses of retinal ganglion cells (RGCs), glial cells, AII amacrine, cone and rod bipolar as well as cone and rod photoreceptor cells confirmed this first assumption. Our results show that all investigated cell types were damaged by ischemia induction. Especially RGCs, cone bipolar cells, and photoreceptor cones are very sensitive to I/R. These cells were lost shortly after ischemia induction with a progressive course up to 7 days. In addition, Müller cell gliosis was observed over the entire period of time. These results provide evidence, that I/R induces damage of the whole retina at early stages and increases over time. In conclusion, our study could demonstrate the intense impact of an ischemic injury. The ischemic defect spreads across the whole retina right up to the outer layers in the long-term and thus seems to impair the visual perception already during the stimulus processing. In addition, our findings indicate that the cone pathway seems to be particularly affected by this damage.